2019
DOI: 10.33369/jeet.3.2.230-248
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of English Pronunciation Errors by English Education Students of FKIP UMSU

Abstract: ABSTRAKPengucapan adalah salah satu hal penting yang harus dikuasai oleh mahasiswa yang belajar bahasa Inggris. Pengucapan yang baik membuat keterampilan berbahasa Inggris mahasiswa menjadi lebih baik. Penelitian ini bertujuan menganalisis kesalahan yang dilakukan oleh mahasiswa jurusan pendidikan bahasa Inggris FKIP UMSU dalam mengucapkan kata-kata bahasa Inggris. Tujuan penelitian ini adalah 1) untuk mendeskripsikan pendapat mahasiswa pendidikan bahasa Inggris tentang kemampuan pengucapan bahasa Inggris mere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
2
12
0
1
Order By: Relevance
“…They sometimes have pronunciation errors when they speak in English. This result was in accordance with studies that found that students still have problems or errors in English pronunciation (C. N. Purba, 2018;Silalahi, 2016;Yusriati & Hasibuan, 2019). The other students (2) were not confident with their English pronunciation.…”
Section: What Is Your Problem With English Learning?supporting
confidence: 90%
“…They sometimes have pronunciation errors when they speak in English. This result was in accordance with studies that found that students still have problems or errors in English pronunciation (C. N. Purba, 2018;Silalahi, 2016;Yusriati & Hasibuan, 2019). The other students (2) were not confident with their English pronunciation.…”
Section: What Is Your Problem With English Learning?supporting
confidence: 90%
“…These errors are common, especially on those English consonants not available in the Filipino sound system. Similarly, errors in pronouncing the sound of the consonant labiodental [v] have been found in the study of Hasibuan & Yusriati (2019). On the other hand, Demircioglu (2013) exemplifies the difficulty of English language learners from Turkey in pronouncing diphthongs in English.…”
Section: Theme 3: Common Pronunciation Errors Of Students In Both Seg...mentioning
confidence: 66%
“…In learning, pronunciation should not be ignored by language teachers. Language learners should always try to improve language skills in the pronunciation of the target language (Yusriati & Hasibuan, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%